INNOVATION AND TECHNOLOGICAL DETERMINANTS OF COMPETITION IN THE ELECTRIC VEHICLE MARKET - Korzh, Maryna; Mokhovikov, Anton (Current Problems of Sustainable Development, 2026)
The article examines the innovation and technological determinants of competitiveness of participants in the global electric vehicle (EV) market under the digital transformation of the automotive industry. The relevance of the study stems from a fundamental change in the sources of competitive advantage in the industry: while in the twentieth century competition was determined mainly by mechanical technologies and economies of scale, the current stage is characterised by a transition to the software-defined vehicle (SDV) paradigm, in which patent potential, software, artificial intelligence and digital ecosystems become the key assets. The aim of the article is to identify the innovation and technological factors of competitiveness in the EV market and to assess the rate of diffusion of electric mobility as an innovative technology. The methodology combines systemic and comparative analysis with the calculation of the Revealed Technology Advantage (RTA) index based on patent statistics, as well as the modelling of innovation diffusion using the S-shaped curve (the E. Rogers — F. Bass model). The empirical base consists of data from the World Intellectual Property Organization (WIPO), the Intellectual Property Owners Association (IPO), BloombergNEF, SDV market analytical reports and the International Energy Agency. The study establishes that the global SDV market will grow from USD 134.7 billion in 2025 to USD 726 billion in 2032 (an average annual rate of 27%), while leadership in patent activity has shifted from traditional manufacturers to the Chinese company BYD (over 50 thousand filed applications). The S-curve analysis proved that no country has taken more than three years to move from 5 % to 15 % of EV share in new sales, evidencing the industry’s entry into the phase of exponential growth. Directions for developing Ukraine’s innovation potential in the relevant segment are substantiated.